Postpartum Anxiety and Stress during the Covid-19 Pandemic - Meliyana, Ernauli; Sirait, Lenny Irmawaty; Suratmi (Future Science / FSH-PH Publications, 2022)
This study aims to obtain information about the anxiety and stress of postpartum mothers during the COVID-19 pandemic. This study used a descriptive survey method on a sample of pregnant women and women giving birth by purposive sampling, namely those who visited the Independent Practice Midwife (BPM) clinic in Bekasi City from April to July 2020, totaling 78 people. Data were collected using the DASS-21 questionnaire which was packaged in a google form and distributed online via WhatsApp social media. The data collected was then analyzed descriptively to be presented as a result of the research. The results showed that the psychological response to anxiety was normal 50 (64.10%), mild 14 (17.95%), moderate 11 (14.10%), severe 2 (2.56%), and very heavy 1 (1.28 %) of respondents. While the psychological response to normal stress was 59 (75.64%), mild 11 (14.10%), moderate 6 (7.69%), and severe 2 (2.56%) experienced psychologically normal but some experienced anxiety and stress. Most of the psychological responses to normal anxiety, but there are mild, moderate, severe, and very severe anxiety, as well as psychological responses to stress, although most normal, there is also mild, moderate, and severe stress.